Effects of variation in dietary contents of selenium and vitamin E on growth and physiological and haematological responses of yellowtail kingfish, Seriola lalandi - Le, K.; Dao, T.; Fotedar, Ravi; Partridge, G. (Springer-Verlag Dordrecht, 2013)
The effects of dietary selenium (Se) and vitamin E and their interaction in the nutrition of yellowtail kingfish, Seriola lalandi, were investigated. Six dietary treatments were prepared in a 3 × 2 factorial arrangement (not supplemented or supplemented with Se at 1 or 2 mg kg-1 × supplemented with vitamin E at 40 or 180 mg kg-1). A group of fish in triplicate were fed one of the six experimental diets for 6 weeks, and their growth performance, haematological and immune responses were measured. The results revealed positively interactive effects between dietary Se and vitamin E in yellowtail kingfish. Se significantly increased weight gain of fish fed diets low in vitamin E, but not high in vitamin E. Simultaneous supplementation of both micronutrients resulted in significant increase in serum bactericidal activity. There was no significant effect of Se or vitamin E on survival, feed intake, feed conversion ratio, haematocrit, white blood cell counts and fillet proximate composition. However, Se and vitamin E contents in fillets were significantly responsive to dietary Se and vitamin E, respectively. The supplemental level of Se at 2 mg kg-1 significantly increased red blood cell counts and haemoglobin concentrations, while lysozyme activity in skin mucus was significantly stimulated by vitamin E. The findings of Se and vitamin E supplementation in this study can be applied to improve growth and health indices of yellowtail kingfish.